EFFICACY AND SAFETY OF THE COMBINATION OF RIBAVIRIN AND PEGYLATED INTERFERON ALFA-2A IN PATIENTS WITH CHRONIC HEPATITIS C: THE RESULTS OF TWO MULTICENTER, PROSPECTIVE, OPEN, NON-COMPARATIVE CLINICAL TRIALS - K. V. Zhdanov; I. G. Bakulin; D. A. Gusev; V. G. Morozov; K. V. Kozlov (Журнал инфектологии)
Aim. Study of efficacy and safety of ribavirin in combination to pegylated interferon α-2a (PegIFN- α-2a) within combined mode of treatment of patients with chronic hepatitis C (CHC) including patients with compensated cirrhosis and and HIV coinfection were conducted. Material and methods. Two open prospective multicenter, non-comparative clinical trials ML16709 NCT00922779 and ML27851 «Standart» (NCT01609049) were conducted. 6661 and 1496 patients with CHC were included accordingly. All were administrated combined therapy: ribavirin and PegIFN- α-2a. Patients with HCV genotype 1 received prescribing treatment for at least 12 but not more than 48 weeks, patients with HCV genotypes 2 and 3 – for at least 12 but not more than 24 weeks. The efficacy analysis included determining the frequency of achieving a rapid virologic response (BVO), an early virologic response (RVO), a virologic response at the end of therapy, and a sustained virologic response (SVR). The safety endpoints were assessed on data of all adverse events (AEs), serious adverse events (SNP), and clinical laboratory findings. Results. At 24 weeks SVR frequency was 43.4% in the subgroup of patients with HCV genotype 1 in the ML16709 study and 72,0% in the ML27851 study; 58,9% and 89,3% in the subgroup of patients with HCV genotypes 2 and 3 accordingly. In the ML27851 study proportion of patients with BVO was 46,8% in patients with HCV genotype 1 and 86,0% in patients with a different HCV genotype. RVO frequency was 37,4% in the subgroup of patients with HCV genotype 1 in the ML16709 study and 90,1% in the ML27851 study; 79,7% and 97,4% in a subgroup of patients with HCV genotypes 2 and 3 accordingly. The proportion of patients with virologic response at the end of therapy was 44,6% in the ML16709 study and 86.7% in the ML27851 study; in a subgroup of patients with genotypes 2 and 3, 73.8% and 97.6%, accordingly. In the ML16709 study 5887 AEs were registered, including 5812 (99%) of non-serious AEs and 75 serious AEs. In the ML27851 study 2557 non-serious AEs occurred in 822 (54.95%) patients. 49 serious AEs were registered in 39 patients (2.6%). Conclusion. The results of studies ML16709 and ML27851 confirm the efficacy and safety of treatment with ribavirin plus peginterferon alfa-2a in patients with chronic hepatitis C. The registered AEs profile is representative of pegylated interferons and ribavirin combination.